Determination of botanical composition, hay yield and forage quality of some natural rangelands in Kyrgyzstan's chuy region - Çınar, S; Abdullayev, A; Esenov, N; Karadağ, Yaşar (Corvinus Univ Budapest, 2020)
This research was carried out in 2018 in order to determine the hay yields, forage qualities botanical compositions and range conditions of 5 different natural rangelands located at different altitudes the Chuy Region, Kyrgyzstan. In the rangelands, the ratio of plant coverage was 96.0-98.0%, the ratio of grasses, legumes, other plant families in the plant covered area was 24.5-48.1%, 4.7-24.0%, 36.2-63.8%, respectively. In the rangelands, the rate of decreaser, increaser and invader species was 37.0%, 7.3% and 55.7%, respectively. The average dry matter yield (DMY) of all five ranges was 2904.6 kg ha(-1), crude protein (CP) was 10.6%, acid detergent fiber (ADF) and neutral detergent fiber (NDF) compositions were 39.1%, 57.1%, respectively. The crude protein yield (CPY) was 307.8 kg ha(-1), digestible dry matter yield (DDMY) was 1699.1 kg ha(-1), and relative feed value (RFV) was 95.3. The rangeland yield increased with altitude. One of the rangelands was in the moderate condition and the others were in poor range condition. According to research results, extensive research targeting appropriate range improvement strategies for each individual rangeland with unique soil and topographic conditions is recommended in order to select among the top seeding, seeding or natural seeding, weed control, grazing methods alone or combined with other range improvement strategies.
Keywords: Central Asia; Range; Yield; Quality; Range condition